A New HPLC-ELSD Method for Simultaneous Determination of N-Acetylglucosamine and N-Acetylgalactosamine in Dairy Foods - Ho Jin Kim; In Kyung Bae; Min Hee Jeong; Hye Jin Park; Jin Sil Jung; Jang Eok Kim (International Journal of Analytical Chemistry)
A rapid high performance liquid chromatographic method with evaporative light scattering detection (HPLC-ELSD), using a carbohydrate column, was developed for simultaneous determination of N-acetylglucosamine (GlcNAc) and N-acetylgalactosamine (GalNAc) in dairy foods. Sample preparation was performed by precipitation using acetonitrile. The limits of detection were 2.097 mg/L for GlcNAc and 3.247 mg/L for GalNAc. The limits of quantification were 6.043 mg/L for GlcNAc and 9.125 mg/L for GalNAc. Accuracy ranged from 96.4 to 105.7% for GlcNAc and from 97.1 to 104.1% for GalNAc. The precision of the method was <1.7% for GlcNAc and <2.2% for GalNAc. The mean recovery of the method was measured by spiking samples with 30.0–120.0 mg/L GlcNAc or 12.5–50.0 mg/L GalNAc and was found to be 95.1–105.5% for GlcNAc and 99.5–105.9% for GalNAc. The stability test results of standard solutions stored at 4, 20, and 40°C were 96.2–104.7% for GlcNAc and 98.0–106.5% for GalNAc. This study determined GlcNAc and GalNAc in dairy foods using HPLC-ELSD method. This rapid, simultaneous quantitation method might be useful as a mean of convenient quality control of dairy foods.